ACHIEVING YOUTH EMPOWERMENT THROUGH REPOSITIONING ENTREPRENEURIAL EDUCATION IN NIGERIAN UNIVERSITIES: PROBLEMS AND PROSPECTS - Aja-Okorie, Uzoma; Adali, Onele (European Scientific Journal, ESJ, 2013)
The overall goal of entrepreneurial education is to impart on students and our youths with the right attitudes, knowledge and skills to act in an entrepreneurial way. Thus, empowering and preparing them to thrive in the unstructured and uncertain nature of today’s environment. This paper therefore, examines the importance of entrepreneurial education in achieving youth empowerment in Nigeria; the challenges facing entrepreneurial education in universities and prospects. The reasons for entrepreneurship education as well as strategies for designing entrepreneurship education are also discussed. This paper argues that entrepreneurial education should not only be addressed at tertiary level but incorporated at all levels of education for an all-encompassing model and in achieving desired goals and ensuring self-releance among Nigerian youths.